Proses Penyelesaian Perkara Perebutan Harta BersamaSetelah Bercerai Studi Kasus di Pengadilan Agama Surakarta - Prahestio, Rio (2016)
This study aims to determine the division of joint property according to Islamic law, customary law, and BW (Burgerlijke Wetboek), describe the consideration of the judge in determining the verdict on the division of joint property of husband and wife after divorce. The method used in this research is a normative method, the type of research is descriptive research. The data source consists of primary data and secondary data. Data were collected through library research and interviews, then analyzed by methods of qualitative analysts. The results showed the position of the plaintiff and defendant are the same magnitude, so between the two sides have the same position to get the treasure together. Consideration of the judge in determining the case proving that the claimant is able to prove the object of dispute, where such property is included in the joint property. Consideration of the judge in determining the verdict in the dispute settlement granted the joint property, so the joint property should be divided equitably the same magnitude.